Some comments on Russia's experiments in cotton cultivation (based on materials from the Turkestan collection) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
These articles report that the success of cotton cultivation in the south of Russia has so far been proven by experiments in the above regions without the use of artificial irrigation.